PERLINDUNGAN HUKUM TERHADAP KURA - KURA SULCATA SEBAGAI SATWA LANGKA BUKAN ASAL INDONESIA DALAM PERSPEKTIF INTERNASIONAL DAN NASIONAL - Jennyver Willyanto; Mella Ismelina Farma Rahayu (Fakultas Hukum Universitas Tarumanagara, 2021)
The existence of animal in this world is needed for human needs and often overused causes the extinction of these animals. One of the activities that occur in the extinction of animals is that trade is carried out not only for endangered animals nationally and internationally. Sulcata tortoise are listed at CITES and IUCN as endangered spesies, at 2018 TRAFFIC report for Indonesia there is still a lot of trade in these endangered species that means Sulcata tortoises can’t be trade without illegal and if want to trade their have to had some permission for trading Sulcata tortoise. The problem is Indonesia doesn’t legally protecting the trade of Sulcata tortoises. Endangered species, so that legally in Indonesia allow these endangered animals to be traded. With this, the question arises how are the legal protection of the Sulcata tortoise internationally and how it is adopted nationally. Internationally, the Sulcata tortoise is said to be an endangered species, so that trade is not permitted arbitrarily without the required documents, but nationally in Indonesia, the Sulcata tortoise is traded widely, causing the population of Sulcata tortoises to decrease. The laws and regulations in Indonesia are not fully regulated protected Sulcata tortoises because the ratification is carried out in the form of a presidential decree so that it is incomplete with the regulations that adhere to the ratification of the international treaty so that it is not only a complete legislation but also the legal structure and legal culture that affect the that matter.